The Effect of Binahong Leaves (Anredera cordifolia) Decoction on Perineal Wound Healing among Post-Partum Women - Shinta Novelia; Siti Syamsiah; Risa Aprilia (KHD Production, 2023)
The puerperium is a period of recovery for the uterine organs as they were before pregnancy as well as physical and psychological changes in the mother. One of the problems during the puerperium is the perineal wound that occurs due to a spontaneous wound or episiotomy during delivery. The wound can be said to be healed if within 1 week the condition of the wound is dry, closed and there are no signs of infection. Delay in the healing time of perineal wounds can be a problem including bladder and birth canal infections. This study aims to determine the effect of water decoction of binahong leaves (Anredera cordifolia) on the healing of perineal wounds among postpartum women at PMB